2019
DOI: 10.1111/gbi.12368
|View full text |Cite
|
Sign up to set email alerts
|

Desert breath—How fog promotes a novel type of soil biocenosis, forming the coastal Atacama Desert’s living skin

Abstract: The Atacama Desert is the driest non‐polar desert on Earth, presenting precarious conditions for biological activity. In the arid coastal belt, life is restricted to areas with fog events that cause almost daily wet–dry cycles. In such an area, we discovered a hitherto unknown and unique ground covering biocenosis dominated by lichens, fungi, and algae attached to grit‐sized (~6 mm) quartz and granitoid stones. Comparable biocenosis forming a kind of a layer on top of soil and rock surfaces in general is summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 60 publications
(82 reference statements)
0
58
0
Order By: Relevance
“…Just like in Africa, the Chilean biocrusts were devoid of cyanolichens [ 35 ], with cyanobacterial members confined to hypolithic habitats [ 51 , 63 ]. Jung et al [ 28 ] described “grit crust”, a transitional form between rock cover and soil crust in a classical sense. Grit crusts are communities consisting of fungi, cyanobacteria and algae, formed on top of singular grit-sized quartz and granitoid stones, which cover and connect the grit-sized rocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just like in Africa, the Chilean biocrusts were devoid of cyanolichens [ 35 ], with cyanobacterial members confined to hypolithic habitats [ 51 , 63 ]. Jung et al [ 28 ] described “grit crust”, a transitional form between rock cover and soil crust in a classical sense. Grit crusts are communities consisting of fungi, cyanobacteria and algae, formed on top of singular grit-sized quartz and granitoid stones, which cover and connect the grit-sized rocks.…”
Section: Discussionmentioning
confidence: 99%
“…Several new cyanobacteria were recently described from the Atacama Desert: Kastovskya, Symplocastrum, Myxacorys, Trichocoleus and Oculatella species [ 23 , 24 , 25 , 26 , 27 ]. The most recent is a study by Jung et al [ 28 ] which investigated the diversity of hypolithic and edaphic cyanobacteria in two study areas, hyperarid Pan de Azúcar and the semiarid area of the Nature Reserve Santa Gracia; the authors reported 21 cyanobacterial species and the new species Aliterella chasmolithica [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that the distribution of terricolous lichens in this desert depends on factors such as distance to the coast, elevation, climatic gradients, wind and sand force, substrate and physiological adaptations [25,47]. The extensive growth of epilithic and crust forming coastal lichens is thought to be supported by moisture content derived from fog and dew [22,23,48]. Water availability has also been considered an important determinant in shaping hypolithic microbial community structure along an inverse fog-…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that the distribution of terricolous lichens in the Namib Desert depends on factors such as distance to the coast, elevation, climatic gradients, wind and sand force, substrate, and physiological adaptations [25,47]. The extensive growth of epilithic and crust forming coastal lichens is thought to be supported by moisture content derived from fog and dew [22,23,48]. Water availability has also been considered an important determinant in shaping hypolithic microbial community structure along an inverse fog-rainfall gradient across the central Namib Desert [4].…”
Section: Discussionmentioning
confidence: 99%